Magnitude or direction? Seasonal variation of interlimb asymmetry in elite academy soccer players - Bishop, C.; Read, P.; Chavda, S.; Jarvis, P.; Brazier, J.; Bromley, T.; Turner, A. (The Journal of Strength and Conditioning Research, 2022)
Previous research has highlighted a distinct lack of longitudinal data for asymmetry. The aims of this study were to provide seasonal variation data for the magnitude and direction of asymmetry. Eighteen elite male academy soccer players (under-23) performed unilateral countermovement jumps (CMJs) and unilateral drop jumps (DJs) during pre-season, mid-season, and end of season time points. Recorded metrics for asymmetry included jump height and concentric impulse for the CMJ, and jump height and reactive strength index for the DJ. The magnitude of asymmetry showed trivial to small changes throughout the season (CMJ effect size [ES] range = -0.43 to 0.05; DJ ES range = -0.18 to 0.41). However, Kappa coefficients showed poor to substantial levels of agreement for the direction of asymmetry during the CMJ (Kappa = -0.06 to 0.77) and DJ (Kappa = -0.10 to 0.78) throughout the season. These data show that when monitoring asymmetry, the magnitude alone may provide a false impression of consistent scores over time. By contrast, monitoring the direction of asymmetry highlights its task and variable nature and is suggested as a useful tool for practitioners who wish to monitor asymmetry over the course of a competitive soccer season.